Graphene bandgap opening by constructing superlattices with BN or MoO2 under pressure. Issue 1 (1st August 2022) - Wang, Bohan; Song, Chaoyang
Abstract: After the isolation of the single layer graphene in 2004, which has overthrown the prediction of the two-dimensional material field, various aspects of its unique properties have been observed, including extremely high strength, carrier mobility and heat conductivity. Being the minority of nonmetallic materials with a conductive property as metals, its possible applications is much widened. Noteworthily, graphene has a zero bandgap. Although making it an excellent conductor, zero bandgap has also constrained its performance as a semiconductor. Fortunately, there are several possible ways to open its bandgap and make it behave like a semiconductor. In this study, we propose that constructing superlattices and controlling hydrostatic pressure to open the bandgap of graphene. Based on first-principles calculations, BN and MoO2 are used to form the superlattice with graphene and 1-30 GPa pressures in the vertical direction of two-dimensional plane are applied. The results show that the pressure can affect the structures and interlayer distances of the superlattice, which further lead to a bandgap of the superlattices containing graphene. Our research shows a method that adjusting the bandgap of graphene through pressure, which is of great significance for the application of graphene in the electronic field.